Adverse Reactions After Intravenous Iron Infusion Among Inflammatory Bowel Disease Patients in the United States, 2010–2014. Issue 8 (13th April 2018) - Akhuemonkhan, Eboselume; Parian, Alyssa; Carson, Kathryn A; Hutfless, Susan
Abstract: Background: Anemia is a frequent complication of Crohn's disease (CD) and ulcerative colitis (UC), collectively known as inflammatory bowel disease (IBD). Intravenous (IV) iron is recommended as the initial therapy for patients with clinically active IBD, severe anemia, and intolerance to oral iron. IV iron is associated with serious adverse effects including a black box warning for anaphylaxis with iron dextran and ferumoxytol. We aimed to examine the occurrence of adverse reactions including anaphylaxis after IV iron infusions in a large database of US IBD patients. Methods: We performed a retrospective analysis for encounters occurring between 2010 and 2014 in MarketScan, a US commercial claims database. We assessed the following adverse events: anaphylactic shock, bronchospasm, and hypotension among IBD patients receiving ferumoxytol, iron dextran, ferric gluconate, iron sucrose, and ferric carboxymaltose. We calculated the adverse event rate per 1000 infusions within 7 days of IV iron infusion. Results: In our study cohort of 6151 IBD patients (38.4% UC), 37 168 IV iron infusions were given (median, 3 infusions). There were very few adverse events; only 1.3% of IBD patients experienced any adverse reaction. The incident rate per 1000 infusions for any adverse event among IBD patients was highest among those receiving ferumoxytol (2.54, 95% confidence interval [CI], 1.26–5.11), ferric gluconate (1.85; 95% CI, 1.03–3.35), iron sucrose (1.74; 95% CI, 1.09–2.78), and iron dextran (0.96; 95% CI, 0.43–2.13). There were 0.24 anaphylactic shock events per 1000 IV iron infusions. Conclusions: About 1.3 of 100 IBD patients ever developed any adverse event. Because adverse reactions are rare, physicians should be encouraged to adhere to recommended guidelines for iron replacement among anemic IBD patients.